The relationship between social status, behaviour, growth and steroids in male helpers and breeders of a cooperatively breeding cichlid - Bender, Nicole (2012)
We tested whether subordinate helper males of the Lake Tanganyika cooperatively breeding cichlid Neolamprologus pulcher show elevated excretion levels of the stress hormone cortisol and reduced levels of 11-ketotestosterone and testosterone when living in groups with a small breeder male, compared to similar helper males living in groups with a large breeder male, in a full-factorial repeated measures experimental design. We also measured the same hormones in breeder males with and without helper males. Previous research showed that the size difference between large male helpers and male breeders in groups of this species influences behaviour and growth decisions. Contrary to our expectation, no effect of the size-difference between helper males and breeder males on helper hormone levels was detected. Furthermore, helper males had similar hormone excretion levels to those of size-matched breeder males without helpers, and to small breeder males. There was no influence of egg laying on breeder male and helper hormone levels during the experiment. Interestingly, all three hormone levels were significantly lower in helpers showing elevated levels of submissive behaviour towards the breeders, independently of the size of the breeder males. The low cortisol levels suggest that helper males can successfully reduce stress by appeasing breeder males through submission. Furthermore, helper males showing a high level of submissive behaviour had lower levels of androgens than less submissive helpers, suggesting a lower reproductive potential in submissive helpers. We propose that helper submission may be used as an honest signal of reduced interest in reproduction towards the breeder male in this species.